ANALISA LOGAM BERAT, KADAR GARAM DAN Salmonella PADA IKAN LOMEK (Harpodon nehereus) BIANG (Ilisha elongata) ASIN KERING - Aulia Azka; Putri Wening Ratrinia (JURNAL PERIKANAN TROPIS, 2020)
Lomek and biang fish are types of fish commonly used as raw materials for making salted fish in Dumai. Industrial activity in Dumai can influence on heavy metal content in dried salted fish. In addition, the requirements for the quality of salted fish are salt concentration and Salmonella test. The aim of this study were to determine heavy metal (Pb and Cd), salt concentration, and Salmonella test in dried salted fish. The study was carried out the preparation of raw materials and the manufacture of salted fish using dry salting method with a salt concentration of 5%, 10% and 15% for lomek and biang fish. The second was the analysis of heavy metal, salt concentration, and Salmonella test. The addition of 10% salt concentration to Lomek fish was the highest result for Pb (1,48± 0,01 ppm), while all samples were not identified for Cd levels. The highest salt concentration was L3 that was 22,45%, while for Salmonella test results all samples were negative. Based on the results, it was concluded that Pb contamination passed the safe limit, while Cd was not detected. The difference in salt addition gave an effect on the salt concentration for dried salted lomek and biang. Salmonella were not found in all salted fish samples.Keywords : Food safety, pathogen, product quality, salted method